The relationship between emotional intelligence, marital and relationship satisfaction among married couples in Johor Bahru - Mohamad Suhaimi Samad; Norashikin Mahmud (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study investigated the relationship between emotional intelligence and marital and relationship satisfaction among married couples in Johor Bahru. A total of 142 married individuals participated in this survey by answering the online questionnaire. The questionnaire consisted of emotional intelligence (33-items), relationship satisfaction (6-items), and marital satisfaction (15-items). Overall, the results showed that married couples in Johor Bahru experience a high level of emotional intelligence and relationship satisfaction and a moderate level of marital satisfaction. The correlation analysis showed a significant positive relationship between emotional intelligence and marital and relationship satisfaction. The study's findings are consistent with the previous literature that supported the notion that emotional intelligence helps married couples gain greater satisfaction through successful communication and resolution of conflict within their marital institution.